Conception of Relation between Intellectual Intuition and Productive Imagination in the Philosophies of I. Kant and J. G. Fichte - Arlauskas, Saulius (Problemos, 1985)
The genesis and the function of two important moments of cognitive activity is disclosed in the manner as they occur in the philosophical systems of I. Kant and J. G. Fichte. Productive imagination and intellectual intuition are defined respectively as theoretical and practical characteristics of the relation between a subject and an object. The author tries to demonstrate the groundlessness of the unconditional detachment of those concepts by I. Kant and by J. G. Fichte. Finally both concepts are linked to the problems of construction of. the dialectical method.